Application of Negotiation Techniques to Actual Cases—An Analysis of International Negotiations on US Foreign Affairs - Wang, Yixuan (Transactions on Economics, Business and Management Research, 2024)
In today’s fast-paced world, the positioning of countries in the global economy underscores the growing influence of international communication and cooperative relations. Central to this development is the essential instrument of negotiation. This paper reviews the case of the negotiations between the United Nations and the United States, which have significantly impacted the global community and international relations. The author explains the importance and utility of negotiation techniques in promoting cooperation, stability, and agreement and examines how these techniques can be efficiently applied in various real-world scenarios. Additionally, the paper investigates the limitations of negotiation techniques when used in isolation and how they interact with other factors. It analyzes how negotiators can enhance their overall competence to achieve better communication results. The article highlights the subtle and ongoing effects of successful negotiations on both the negotiators and the parties they represent. This case study aims to contribute to the enhancement of effective communication between nations and individuals and to popularize the use of bargaining skills and mindsets. By doing so, it seeks to enable the general public to maximize mutual benefits more efficiently during negotiations. This research not only provides insights into the practical application of negotiation strategies but also underscores their broader implications for international diplomacy and cooperation.